The The Most frequent surgical and post-surgical complications in impacted teeth surgery - Sucari, Max; Machaca, Edison; Padilla, Tania (Revista Acciones Médicas, 2023)
This article aimed to collect data on the most common surgical and post-surgical complications associated with retained tooth surgery. We present a range of concepts related to surgical complications and retained teeth, including indications and contraindications. The methodology for this literature review focused on authors who have addressed various surgical complications and their favorable and unfavorable outcomes. Finally, we detail the association between surgical complications and retained teeth, revealing that 13% of surgical patients experienced postoperative complications.
Keywords: impacted canine; impacted third molar; impacted tooth; surgical complications